Developing a specialised strategy framework to improve performance in traffic department of Abu Dhabi Police - Alwali Almazrouei, Abdulla Nasir Ali (2021)
The United Arabs Emirates has, over the last decade, adopted a more open economic approach, and this has made the UAE experience a significant cultural diversity from the global communities, alongside the increased flow of technology into the country. Due to these changes, the police service has been facing unique challenges in traffic management, leading to the development of a specialised strategy for Abu Dhabi Police (ADP) to overcome traffic issues. Previous studies have investigated traffic accidents and traffic death rate; however, there is no clear evidence for any research that has investigated the role of the specialised strategies in improving police performance to mitigate traffic issues. Therefore, this study seeks to identify the factors of ADP’s specialised strategy and assess its impact on police performance regarding reducing road traffic accidents and traffic death rate. The eventual aim is to develop a framework to improve the performance of police through a specialised strategy. So, simple random sampling has been used in this study to collect the data. A total of 335 completed questionnaires were returned. Finally, 260 survey sets were considered valid for analysis while the others are invalid for inclusion in the study. Based on the literature review and descriptive analysis of the first research objective, the results showed that there are four factors associated with ADP’s specialised strategy: Learning and training, Traffic setting, Emergency response, and Road engineering and road safety. Analysis of Moment Structures Equation Modelling (AMOS-SEM) model was developed based on the study hypothesis related to ADP performance to answer the second research objective. The findings showed there is a relationship between the specialised strategy factors and police performance since the four hypotheses of the study were supported. The third objective was achieved based on the results of the first research objective to develop a propsed framework to enhance police performance and reduce traffic accidents and, therefore, traffic accidents death rate. Thus, with reference to the relationship between the objectives of this study, the Structural Equation Model (SEM) and the hypotheses set for this study, it can be concluded that the framework of the third research objective supports the specialized strategies improvement mechanism in Abu Dhabi police performance which can be achieved using the factors of the specialised strategy investigated in this study. The findings from this study have provided proof that road strategic management is essential to improve police performance. Besides, every country needs to adapt the developed specialised strategies according to the country's needs and resources.